Liver transplantation for hilar inflammatory myofibroblastic tumor: Case report and review of the literature. (27th November 2022) - Costa, Carolina Magalhães; Neto, João Seda; Benavidez, Marcel R.; Vincenzi, Rodrigo; Roda, Karina; Oliveira, Caio Márcio V.; Travassos, Nathália Porto R.; de Lima, Luiz Guilherme C. A.; Pereira, Fabio Payão; Fonseca, Eduardo A.
Abstract: Background: Inflammatory myofibroblastic tumors (IMTs) of the liver are rare neoplasms. These tumors are difficult to distinguish from other neoplasms by radiological examination, have uncertain evolution, and there is no consensus on the treatment of these lesions. Hilar tumors can involve the portal vein, hepatic artery, bile duct, and spread to the branches of the portal triad, causing obstructive symptoms, occlusive phlebitis, and portal hypertension. Thus, liver transplantation (LT) is an excellent alternative for locally advanced hilar tumors, since it ensures complete tumor resection with free margins. Methods/Results: We present a literature review and a case report showing a 3‐year‐old boy with liver IMT invading the hepatic hilum and inferior vena cava, who underwent a successful living donor liver transplantation that required portal vein and vena cava replacement. Conclusion: The incidence of hilar IMTs is low and there is no well‐established standard treatment. Liver transplantation for a hilar tumor with vascular invasion was acceptable in this case because the radically of the surgery was the key for the cure, and because the tumor was benign in nature.